2022
DOI: 10.1007/s40120-022-00407-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analyses Identify KCNJ15 as a Candidate Gene in Patients with Epilepsy

Abstract: Introduction: Although there is accumulating evidence that genetic factors play a vital role in the pathogenesis of epilepsy, few epilepsy-associated genes have been identified. Additionally, the role of KCNJ15 in epilepsy has not been evaluated so far. Methods: Here, we performed differentially expressed gene analysis, expression quantitative trait loci analysis, gene co-expression analysis, and protein-protein interaction analysis to evaluate the role of KCNJ15 in epilepsy. Results: Analysis of gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The activation of the Kir4.2 channel is extracellular K + -and intracellular pH-dependent with a single-channel conductance of ~25 pS and high open probability (P o ≈ 0.7-0.9) when the homotetrameric Kir4.2 is expressed in Xenopus oocytes (Pessia et al 2001, Edvinsson, Shah andPalmer 2011). Although Kir4.2 is broadly expressed in various organs including the kidney, stomach, pancreas, and brain, its physiological functions remain largely elusive (Lourdel et al 2002, He et al 2011, Okamoto et al 2012, Wang et al 2022. It was only shown to inhibit insulin secretion in pancreatic β cells (Okamoto et al 2010, Okamoto et al 2012, regulate gastric acid secretion (He et al 2011, Yuan et al 2015, and may play an active role in epilepsy (Wang et al 2022) and wound healing through regulating galvanotaxis (Nakajima et al 2015, Nakajima andZhao 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the Kir4.2 channel is extracellular K + -and intracellular pH-dependent with a single-channel conductance of ~25 pS and high open probability (P o ≈ 0.7-0.9) when the homotetrameric Kir4.2 is expressed in Xenopus oocytes (Pessia et al 2001, Edvinsson, Shah andPalmer 2011). Although Kir4.2 is broadly expressed in various organs including the kidney, stomach, pancreas, and brain, its physiological functions remain largely elusive (Lourdel et al 2002, He et al 2011, Okamoto et al 2012, Wang et al 2022. It was only shown to inhibit insulin secretion in pancreatic β cells (Okamoto et al 2010, Okamoto et al 2012, regulate gastric acid secretion (He et al 2011, Yuan et al 2015, and may play an active role in epilepsy (Wang et al 2022) and wound healing through regulating galvanotaxis (Nakajima et al 2015, Nakajima andZhao 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although Kir4.2 is broadly expressed in various organs including the kidney, stomach, pancreas, and brain, its physiological functions remain largely elusive (Lourdel et al 2002, He et al 2011, Okamoto et al 2012, Wang et al 2022. It was only shown to inhibit insulin secretion in pancreatic β cells (Okamoto et al 2010, Okamoto et al 2012, regulate gastric acid secretion (He et al 2011, Yuan et al 2015, and may play an active role in epilepsy (Wang et al 2022) and wound healing through regulating galvanotaxis (Nakajima et al 2015, Nakajima andZhao 2016). However, little is known about the biochemical properties of this channel protein and how they are affected by disease-associated mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The inwardly rectifying potassium channel, subfamily J, member 15 ( KCNJ15 ) gene, which encodes Kir4.2 channel, has been identified to have an inhibitory effect on insulin secretion in pancreatic β cells by maintaining the resting membrane potential of these cells, thereby inhibiting depolarization processes involved in insulin release. Kir4.2 is the most prominently expressed among all K + channels in the stomach, playing a pivotal role in regulating gastric acid secretion. , The KCNJ15 gene resides within the Down syndrome chromosome region 1 on chromosome 21 and has been implicated in the pathogenesis of Down syndrome. , Previous studies have also suggested that its involvement is not limited to metabolic disorders and Down syndrome, but also extends to the pathogenesis of several central nervous system diseases . It has been implicated as a potential biological target for Parkinson’s disease, Alzheimer’s disease, and epilepsy, suggesting that it is involved more broadly in the pathogenesis of central nervous system disorders. Despite the significance of Kir4.2 as a molecular target, the number of its identified ligands remains limited. Only a few compounds, including polymyxins B and VU0134992, have been reported to interact with Kir4.2. , However, there are currently no specific Kir4.2 modulators available, making it challenging to selectively activate or inhibit the channel functions for mechanistic studies.…”
mentioning
confidence: 99%
“… 11 , 12 Previous studies have also suggested that its involvement is not limited to metabolic disorders and Down syndrome, but also extends to the pathogenesis of several central nervous system diseases. 13 It has been implicated as a potential biological target for Parkinson’s disease, Alzheimer’s disease, and epilepsy, suggesting that it is involved more broadly in the pathogenesis of central nervous system disorders. 13 15 Despite the significance of Kir4.2 as a molecular target, the number of its identified ligands remains limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation